2022
DOI: 10.3847/1538-4357/ac7463
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Shapes of Brightest Cluster Galaxies

Abstract: We discuss the statistical distribution of galaxy shapes and viewing angles under the assumption of triaxiality by deprojecting observed surface brightness profiles of 56 brightest cluster galaxies (BCGs) coming from a recently published large deep-photometry sample. For the first time, we address this issue by directly measuring axis ratio profiles without limiting ourselves to a statistical analysis of average ellipticities. We show that these objects are strongly triaxial, with triaxiality parameters 0.39 ≤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…But there has also been interest in the inner region of haloes (e.g. de Nicola et al 2022). We find that the CDM haloes (left-hand side) are more elliptical than the fSIDM haloes (right-hand side).…”
Section: Simulated Haloesmentioning
confidence: 73%
See 1 more Smart Citation
“…But there has also been interest in the inner region of haloes (e.g. de Nicola et al 2022). We find that the CDM haloes (left-hand side) are more elliptical than the fSIDM haloes (right-hand side).…”
Section: Simulated Haloesmentioning
confidence: 73%
“…It is crucial to be aware of this when comparing simulation results to observations. For example, the deprojection algorithm of de Nicola et al ( 2020) allows observed galaxies to be inferred and it can be used for comparison (de Nicola et al 2022). Interestingly, de Nicola et al (2022) found the shape in the most inner region of the brightest cluster galaxies to become more elliptical, which is in contrast to previous findings where the baryons were found to make haloes more spherical (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…SHAPE3D is able to constrain the range of possible orientations of a triaxial galaxy based on photometric information alone by discarding deprojections where the radial profiles of the flattenings p b a = / and q c a = / (with a being the semimajor, b the semi-intermediate, and c the semiminor axes of a triaxial galaxy) are not smooth (de Nicola et al 2020(de Nicola et al , 2022b. When deprojecting the observed SB of NGC 5419 we apply an rms cutoff rms= ( ( ))  I I ln 0.013 obs fit 2 á ñ for the maximum discrepancy between the observed and modeled surface brightnesses.…”
Section: Triaxial Dynamical Modelingmentioning
confidence: 99%
“…For the purely photometric results, we compare the shape profiles yielded by the deprojections using a similar approach as in de Nicola et al ( 2022), i.e. we consider every deprojection that is qualified as good according to the criteria given in de Nicola et al (2022) and calculate the average < 𝑝(𝑟) >, < 𝑞(𝑟) > among them. The range encompassed by these 'good' deprojections is shown by light-coloured regions in Fig.…”
Section: Shape Recoverymentioning
confidence: 99%
“…Finally, we show how the possible viewing angles of a galaxy can be significantly reduced from photometry alone. This not only helps the dynamical modeling, but also allows us to directly estimate galaxy shapes from photometry alone (de Nicola et al 2022).…”
Section: Introductionmentioning
confidence: 99%